A critical study on the intention to create legal relation in domestic agreement / Muhammad Rejabhadb Kamarolzaman … [et al.] - Kamarolzaman, Muhammad Rejabhadb; Azmi, Nur Dalila Husna; Nawi, Muhammad Iqbal; Abdul Rashid, Khairul Amir (2014)
Domestic agreement can be defined as an agreement reached between two people living in a family relationship, which outlines their particular rights and responsibilities. Domestic agreement can be categorized into two categories which are agreement between spouses and agreement between parent and child. Domestic agreement is not intended to have legal consequences. In domestic agreements, for example, those made between husbands and wives and parents and children, there is presumption of no intention to create legal relations and the agreement should be not be subjected to litigation. Under the cover of domestic relations, the promisor can exploit the promisee without any obligation enforceable in the court of law by the promisee against the promisor. However, there are situation where the court that the agreement is legally bound between the parties. Thus, the courts are not consistent in determine the intention to be legally bound in such promise made in the domestic agreement. In this project paper, we will discuss about the issue of domestic agreement and its legal consequences. We will also introduced a standard guidelines pertaining to the case decision in the domestic contract. We hope this research study can be used to protect the right of contractual parties and also could be used by the judges pertaining to intention to create legal relation in domestic agreement.